In I Subjected to Father's Violence Shame Confusion - (:unkn) unknown (ILEM, 2022)
In this study, it was tried to reveal the perceptions of shame about violence of women who were subjected to violence by their fathers in childhood. Interpretative phenomenological analysis method was used in the research. The study group consists of four people selected by criterion sampling. The criteria are determined as being subjected to violence by the father during childhood or to be a witness, to be married, to have a child and being participating in the psychodrama experience group organized on motherhood-womanhood roles. Semi-structured interviews were held with the participants. In the process of analyzing the data obtained, the interpretive phenomenological analysis stages were followed. Themes obtained as a result of interviews with women who witnessed or experienced violence by their fathers in childhood as follows; reactions to the father who applied violence during their childhood and shame about sharing the experience of violence For example, the narratives of participants in the study show that they had unwanted and shameful father images in their minds. The humiliation, belittlement, etc. attitudes of the father towards the child have created shame and it is a situation that should be examined in later researches through various personality structures.
Keywords: Patriarchal violence; shame; child abuse; domestic violence; qualitative research; WOMEN; GUILT